Dynamic delayed detached eddy simulation of a multi‐inlet vortex reactor. Issue 7 (23rd March 2016) - Liu, Zhenping; Passalacqua, Alberto; Olsen, Michael G.; Fox, Rodney O.; Hill, James C.
Abstract : The multi‐inlet vortex reactor (MIVR) is used for flash nanoprecipitation to manufacture functional nanoparticles. A validated computational fluid dynamics model is needed for the design, scale‐up, and optimization of the MIVR. Unfortunately, available Reynolds‐averaged Navier‐Stokes methods are unable to accurately model the highly swirling flow in the MIVR. Large‐eddy simulations (LES) are also problematic, as excessively fine grids are required to accurately model this flow. These dilemmas led to the application of the dynamic delayed detached eddy simulation (DDES) method to the MIVR. In the dynamic DDES model, the eddy viscosity has a form similar to the Smagorinsky sub‐grid viscosity in LES, which allows the implementation of a dynamic procedure to determine its model coefficient. Simulation results using the dynamic DDES model are found to match well with experimental data in terms of mean velocity and turbulence intensity, suggesting that the dynamic DDES model is a good option for modeling the turbulent swirling flow in the MIVR. © 2016 American Institute of Chemical Engineers AIChE J, 62: 2570–2578, 2016